Corrections to: Checkpoint inhibitor therapy for cancer in solid organ transplantation recipients: an institutional experience and a systematic review of the literature. Issue 1 (24th June 2019) - Abdel-Wahab, Noha; Safa, Houssein; Abudayyeh, Ala; Johnson, Daniel H.; Trinh, Van Anh; Zobniw, Chrystia M.; Lin, Heather; Wong, Michael K.; Abdelrahim, Maen; Gaber, A. Osama; Suarez-Almazor, Maria E.; Diab, Adi
Abstract : Following publication of the original article [1], the authors reported an error in the Acknowledgments section. It should be read: 'We are grateful to Mohsin Shah from the Department of Emergency Medicine at The University of Texas MD Anderson Cancer Center for assisting in study selection, and to Gregory F. Pratt from the Research Medical Library and Erica Goodoff, from the Department of Scientific Publications at The University of Texas MD Anderson Cancer Center for their valuable contributions.